Mitigating bureaucratic inefficiencies through blockchain technology in Africa - Shava, Elvin; Mhlanga, David (Frontiers in Blockchain, 2023)
With the Fourth Industrial Revolution (4IR) wave engulfing African governments, the need to do, and use something new has already infiltrated many public sector organizations. While modern technologies are being embraced in the private sector, African governments are emulating new technologies and other Information Communication Technologies (ICTs) to advance their economies while managing the risk that these sophisticated technologies can trigger. Blockchain technology is one of the emerging 4IR technology that is believed to have the capacity to mitigate bureaucratic inefficiencies, although scholars argue implementing such comes at a higher price. To understand how blockchain can help reduce inefficiencies in African bureaucracy, the researchers employed the systematic literature review analysis where documents from various databases such as Scopus, Web of Science, and Google Scholar were systematically sampled depending on how they offer meaningful data concerning blockchain implementation. The analyses of these secondary sources revealed multiple challenges and opportunities associated with blockchain technology in the African government. The challenges include poor project management, weak institutions that do not uphold accountability and transparency in data entry using blockchain, unavailability of blockchain infrastructure, risk-averse attitude, and absence of institutional readiness. By implementing enabling technology policies in government, the study revealed that blockchain could help improve taxation in African bureaucracies and mitigate data altering and errors while maximizing efficiency. Further merits in public healthcare and education can be realized by using blockchain technology. The conclusions drawn from this study have shown that for African bureaucracy to thrive using blockchain technology, there is a need to prepare public sector institutions to embrace blockchain technology. At the same time, investment in soft and technical skills remains fundamental to mitigate inefficiencies in public service provision. Institutional readiness is another deterrent to blockchain technology as public administration regard this technology as demanding since it may require change, management where institutions and structures are reshuffled to respond to the demands of the blockchain technology in the delivery of public goods.